Utilizing Mobile Applications for 21st-Century Learning and Digital Preservation of Balinese Script - Asroni, Ahmad; Putu Ade Pranata; Gede Indrawan; Luh Joni Erawati Dewi; Daniel Kevin Alexander (Sinkron : jurnal dan penelitian teknik informatika, 2025)
Balinese Script and other inheritance local languages are facing extinction signalment since their use has already been replaced by their national languages, which are simpler and more practical. Bali province has already had governor regulations to preserve this local wisdom through many efforts in Bali, including conducting compulsory local content subject Balinese language (covering Balinese Script) from primary to high school, requiring institution's nameplates to be written in Balinese Script along with different languages, etc. This collaborative study, a joint effort between language and computer science, has exposed the technological side of support for preservation efforts. Through the mobile application from a smartphone, this study revealed the advantage of using this proposed Information Technology application for 21st-century learning of Balinese Script, including paperless material to conduct green-and-sustainable-oriented learning and efficiency to grab knowledge in real-time related to the transliteration and translation aspects from Latin text input. That effort was considered the main contribution to this research area.